(untitled) (Praxis Educativa, 2021)
My intention is to consider Bernard Stiegler’s concept of “journeys of knowledge” (Stiegler, 2020a) in the wake of the experience of confinement in the time of the corona virus pandemic. I reflect on this during the time of the corona virus in my own isolation, withdrawal, confinement and loneliness because my interest in the concept of “journeys of knowledge” lies in how to use the internet in bifurcatory ways to produce what Stiegler calls “negentropic knowledge,” or new forms of knowledge, or what I want to designate as experiments with truth-telling. With the above in mind, it is by rethinking the concept of curation in a different way that it is hoped I can contribute to educational research and produce my own bifurcation of knowledge.